Evaluation of circulating osteopontin levels in an unselected cohort of patients with multiple sclerosis: relevance for biomarker development. (April 2014) - Kivisäkk, Pia; Healy, Brian C; Francois, Katiana; Gandhi, Roopali; Gholipour, Taha; Egorova, Svetlana; Sevdalinova, Velina; Quintana, Francisco; Chitnis, Tanuja; Weiner, Howard L; Khoury, Samia J
Background: Osteopontin (OPN) is a pleiotropic protein with important roles in inflammation and immunity that has been suggested as a candidate biomarker for disease activity in multiple sclerosis (MS). Objective: We evaluated plasma levels of OPN in an unselected cohort of MS patients, to determine its potential as a biomarker for disease subtype and/or disease activity in a regular clinical setting. Methods: We analyzed OPN plasma levels in 492 consecutive MS patients, using a commercial enzyme-linked immunosorbent assay (ELISA). Results: OPN levels were higher in relapsing–remitting and secondary progressive MS, compared to healthy controls. Treatment with natalizumab or glatiramer acetate was associated with lower OPN levels. There was no significant association between the OPN levels and disease activity, as measured by clinical or radiological criteria. One-third of patients with high OPN levels had concurrent disorders that may also be associated with increased OPN expression, and which may mask a modest effect of MS disease activity on OPN levels. Conclusion: Our data do not support a role for circulating OPN levels as a biomarker for disease activity in a heterogeneous clinical setting, but does not rule out a potential role in the cerebrospinal fluid, in a controlled setting such as a clinical trial, or in concert with other biomarkers.